Agile innovation : the revolutionary approach to accelerate success, inspire engagement and ignite creativity - Morris, Langdon; Ma, Moses, 1956-; Wu, Po Chi, 1948- (2014)
"Effective innovation doesn't happen by accident - it happens by design! Agile Innovation is the field guide to designing and implementing effective innovation methods and projects, and facilitating collaborative processes that enable people to solve complex problems and create breakthrough solutions. The book offers a comprehensive Innovation Master Plan Framework, which provides five critical performance areas and how to optimize them for sustained innovation improvement. Agile Innovation teaches how to discover and develop better ideas, learn and work together more profitably and effectively, and create breakthroughs"--
Machine generated contents note: About this Book Mastery of Innovation Why Don't Large Firms Innovate? Part 1: The Innovation Revolution 1. Starting at Sprint Zero: A Better Way to Innovate Wait, Is There... Resistance to Change? The Secret Sauce of Innovation Be Your Own Revolution 2. Becoming Agile Rapidly and Painlessly Individuals and Interactions Adapt or Die The Challenge 3. Transforming How We Work Innovating Is Learning Transforming Ideation From Insight to Disruption The World is Changed Transforming Execution: From Assumptions to Evidence Transforming Time: From Meetings to Productivity Transforming Organizations Summary: Eight Organizational Principles 4. Thriving in Change Defining the Innovation Process Change and Mindset A Framework for Transformation The Innovation Master Plan Part 2: Managing Innovation for Tomorrow 5. Accelerating Success The Need for Speed The Scrum and the Sprint The Agile Software Sprint Innovation and Extreme Sports at Wells Fargo Uncertainty The Agile Innovation IdeaScrum Social Workflow The Research Cycle The Research Cycle: Needfinding, Modeling, Ideation, and Prototyping Proactive Innovation The Customer Value Proposition The Agile Innovation Process Facilitating the Workflow Spontaneous Innovation Gathering Feedback 6. Reducing Innovation Risk A System for Innovation Strategy for Agile Innovation Four Types of Innovation Innovation Portfolio Design Portfolio Success Factors Measure to Manage Broader Innovation Portfolio Metrics Automating Portfolio Management Redux: The Pivotable Portfolio Summary 7. Engaging with Collaborative Teams Transcending Limitations What Is Innovation? People Are the Core The Key Elements of the Innovation Culture The Right People The Right Skills The Right Roles in the Innovation Culture Creative Genius Agile Innovation Champions Agile Innovation Leaders Promoting Comprehensive Transformation at Wells Fargo Summary: Innovation Culture Metrics 8. Building Agile Innovation as a Core Competence Facilitating and Managing Collaboration Removing Roadblocks Orchestrating Team Rhythm Innovation is a Team Sport Summary: Courage Is a Core Competence Part 3: Leading the Revolution: From Plans to Action Innovate As If Your Life Depends on It 9. Developing Agile Leadership How Apollo 13 Was Able to Return to Earth Is Failure an Option? Leadership and Uncertainty Don't Settle The Self-Actualized Innovator Maslow's Hierarchy of Needs Self-Actualizing Organizations Metavalues Action Steps: It's All About Leadership What Is Your Passion? 10. Cultivating Core Creativity Seeing More Deeply Multi-Visioning Great Stories Practice From Fear to Flow 11. Achieving an Iconic Brand Branding and Totems Overcoming Brand Blind Spots: A Case Study Brands and Archetypes Storytelling The Business Panorama Creating Your Icon 12. Optimizing your Infrastructure Four Elements of Infrastructure Exploration and Production Dealing with Uncertainty The Virtual Infrastructure The Virtual Workplace Engagement in a Shared Mental Space Facilitating Innovation The Physical Work Place for Innovation Summary 13. Advancing Open Innovation Engaging Smart People in Your Innovation Effort Agile + Open = Ecosystem Innovation Openness in Business Ecosystems Technology-Enabled Openness IdeaXML The Next Generation Toolset The Promise of Intelligent Openness 14. Traveling the Road to Revolution Ten (Easy) Steps The Revolutionary Leader: What Kind of Revolutionary are YOU? The Power of Commitment Conclusion: Using Agile Strategy to Shape Your Organization's Future Acceleration Agile Strategy: The Evolution of Innovation Three Eras of Innovation Tools Agile Strategy and the Acceleration of History The Approaching Singularity The Agile Economy Our Conclusion: Innovation Is Not Imitation Agile Capitalism Appendix A: Critical Questions Personal questions Innovation as a process Corporate culture/management Competition Intellectual Property Customers Appendix B: Resources for Your Revolution Appendix B: Definitions .
Includes index.
Keywords: Organizational change; Creative ability in business; Success in business; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management